An evaluation of teachers' ability to identify children with motor difficulties - Gritzman, Tamara (My University, 2013)
Background: Children with Developmental Coordination Disorder present with motor difficulties that affect their activities of daily living, academic and social function, with both short- and long-term consequences. Referrals for therapy are often made by class teachers, which is necessary for further assessment and initiating intervention. Objective: To evaluate whether teachers are able to identify motor difficulties among the children in their class. Methods: Sixteen teachers at seven schools were approached. Several children were randomly chosen from each class. Once parental consent had been obtained, children were tested on the Movement Assessment Battery for Children Second Edition (MABC-2). The results were compared to a brief teacher questionnaire on each child’s motor ability. Results: Overall the teachers’ sensitivity was 0.33 and specificity was 0.75, which is below the recommended level for a screening tool. Teachers had a tendency to over-score (overestimate) a child’s ability for Manual Dexterity, but under-score (under-estimate) for Aiming and Catching and Balance. No significant difference (p<0.05) was found relating to teacher education level, or a teacher’s confidence in her ability to identify children with motor difficulties. Overall prevalence, at 20 percent, was found to be higher than the APA (2000) reported statistic of six percent. Information regarding teachers’ opinions of what constituted motor difficulties was obtained, but a detailed analysis of why this was so was not in the scope of this research. Conclusion: Teachers are not adequately able to identify children with motor difficulties from their class. They were unable to distinguish between those presenting with difficulties and those without. An alternative system to identify children with motor difficulties should be investigated. Key words: Developmental Coordination Disorder (DCD); motor difficulties; Movement Assessment Battery for Children Second Edition (MABC-2); teachers.